Pengaruh Latihan Kecepatan dalam Lari Sprint Menggunakan Permainan Tradisional - Amanah Illahi, Pandu; Dinar Dinangsit; Encep Sudirjo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the influence of traditional games of boi-boian, cat and rat, as well as red-green lights on increasing the speed of sprint running of grade VI students of SD Negeri Tegalendah. The method used was a pre-experiment with a one group pretest-posttest design, involving 26 grade VI students selected through purposive sampling. The research instrument was in the form of a 60-meter sprint test with a score of 1–10, and the data were analyzed using the normality test, the pair sample t-test, and the R-square test. The results showed that there was a significant increase in the speed of the students' sprints, with the average score from 57.30 in the pretest to 64.23 in the posttest. Normally-distributed data, the significance value of the t-test of 0.002 (p < 0.05) confirms the statistically significant score difference. In addition, the R Square value of 0.550 shows that the application of three variations of traditional games has a very large influence, namely 55.0%, on improving students' sprint running ability. In conclusion, traditional game-based learning has been proven to be effective in improving students' motor skills, making the exercise process more lively, fun, and encouraging active engagement. Thus, physical learning focuses not only on speed, but also on the development of motor skills as a whole. Keywords: Sprint Running, Traditional Games, Game Variation